Contribution to the Uropodina mites of Peru (Acari: Mesostigmata) - Kontschán, Jenő; Friedrich, Stefan (Zootaxa, 2017)
Soil dwelling Uropodina mites were collected from a primary lowland rainforest in Amazonian Peru. The species found belong to three different families. A new diagnosis and the type genus of Tetrasejaspidae fam. nov. are given, and the family is recorded from Peru for the first time on the basis of Tetrasejaspis sellnicki Hirschmann, 1973. Two rotundabaloghid mites were collected (Rotundabaloghia (Circobaloghia) magna Hirschmann, 1992 and Rotundabaloghia (Circobaloghia) iquitosensis Hirschmann, 1992), both already reported from Peru. A new species (Origmatrachys peruensis sp. nov.) from the family Trachyuropodidae was collected in large numbers from soil, and is described on the basis of females, males, nymphs and larvae. This is the first description of the protonymphs and larvae of Origmatrachys. The new species differs from the previously described ones in the basis of sculptural pattern of dorsal, ventral, sternal shields and the length of the setae in the central part of the dorsal shield. A new key to the known adults and deutonymphs of Origmatrachys is given.